High performance of Co3O4@carbon composites as anodes for Lithium‐ion batteries. Issue 8 (8th April 2022) - Xie, Huan; Yang, Guang; Cai, Zhenyu; Li, Ze; Wang, Yinwei
Abstract: BACKGROUND: Metal oxides suffer from huge volume changes and poor electrical conductivity as anode materials in lithium‐ion batteries. Many nanostructures have been designed to improve the electrochemical performance of metal oxide anodes. RESULTS: In this work, Co3 O4 @carbon composites are prepared via hydrothermal reaction. The as‐prepared Co3 O4 @carbon composites displayed good lithium storage performance and excellent cycling stability. The Co3 O4 @carbon anode showed a high capacity of 986 mAh/g after 100 cycles at 0.2 C. CONCLUSION: The superior electrochemical performance of the Co3 O4 @carbon anode is attributed to its unique hybrid structure, which can improve electrical conductivity and act as a buffer for the volume change during electrochemical reactions. © 2022 Society of Chemical Industry (SCI).